1997
DOI: 10.1007/bf00175263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital color deficiencies in secondary-school students in Tehran

Abstract: Purpose.A population-based study was conducted to determine the prevalence of color deficiencies in secondaryschool students (ages 12-14) in Tehran. Methods. A total of 2058 students (1136 males, 922 females) were examined with Ishihara pseudoisochromatic color plates. Results. In the study population, 97 cases of defective color vision were detected, including 93 males and 4 females. The affected individuals all had negative histories of previous systemic and ocular disease or chronic use of medications. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
5
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 1 publication
3
21
5
2
Order By: Relevance
“…Results from all these studies situated within the anticipated range for Caucasian males; about 8.0-10.0% of the Caucasian male population is affected [14]. CVD prevalence in neighboring countries are either lower or higher than this study results as (8.72) in Jordan [15] , In Iran, three studies are done in different cities in Qazvin, Zanjan , and Tehran, the prevalence of CVD were varied from 3.49 to 8.7 and 8.8 respectively [16][17][18],7.3% in Turkey [19], and 2.9-11% in Saudi Arabia [20][21]. In some European countries, in three different studies, the prevalence of CVD among male students in Germany were (7.8), (7.95) among males in Greek and (8.7) among males in Denmark [22][23][24].…”
Section: Discussionmentioning
confidence: 85%
“…Results from all these studies situated within the anticipated range for Caucasian males; about 8.0-10.0% of the Caucasian male population is affected [14]. CVD prevalence in neighboring countries are either lower or higher than this study results as (8.72) in Jordan [15] , In Iran, three studies are done in different cities in Qazvin, Zanjan , and Tehran, the prevalence of CVD were varied from 3.49 to 8.7 and 8.8 respectively [16][17][18],7.3% in Turkey [19], and 2.9-11% in Saudi Arabia [20][21]. In some European countries, in three different studies, the prevalence of CVD among male students in Germany were (7.8), (7.95) among males in Greek and (8.7) among males in Denmark [22][23][24].…”
Section: Discussionmentioning
confidence: 85%
“…Uluslararası yapılan çalışmala-rın sonuçları incelendiğinde, Modarres ve ark. (19) %8,18'inde (93), kız öğrencilerin %0,43'ünde (4), Horace (20) erkek öğrencilerin %6,2'sinde, kız öğren-cilerin %0,55'inde renk körlüğü olduğunu belirlemiş-lerdir. Türkiye'de yapılmış çalışma sonuçlarıyla bulgularımızın örtüştüğü belirlenirken, farklı ülkelerde yapılan araştırmalarla olan farklılığın toplum özellik-lerin farklı olması ve sağlık hizmetlerinden yararlanma düzeylerinin eşit olmamasının tarama sonuçları üzerinde etkili olabileceği düşünülmektedir.…”
Section: Discussionunclassified
“…Modarres ve ark. 'nın (19) yapmış oldukları çalışmada, araştırmaya katılan erkek öğrencilerin %8.18'inde (93), kız öğrencilerin %0.43'ünde (4) renk görme bozukluğu olduğunu saptanmıştır. Horace (20) yapmış olduğu çalışmada, araştırmaya katılan erkek öğrencilerin %6,2'sinde, kız öğrencilerin %0,55'inde renk görme bozukluğu olduğunu belirlemiştir.…”
Section: Discussionunclassified
“…Grassivaroet al [7] reported a color blindness frequency of 4.9%. In a population based study of prevalence of Congenital Color deficiencies in Secondary School Students in Tehran, carried out by Modarres M, Mirsamadi M, Peyman GA [8] , 2058 secondary school students(1136 males & 922 females) in Tehran were examined with Ishihara Pseudoisochromatic Color Plates and total 97 cases of defective color vision (93 males & 4 females) were detected. Of the 93 cases (8.18%) of defective color vision in male, 56 cases (4.93%) had deuteranomaly, 13 cases (1.14%) protanomaly, 13 cases (1.14%) deuteranopia & 11 cases (0.97%) protanopia.…”
Section: Discussionmentioning
confidence: 99%